El Pueblo de Nuestra Señora la Reina de los Ángeles de la Porciúncula: Or How Los Angeles Got its Name - Aronberg Lavin, Marilyn (Religion and the arts, 2014)
‭This study traces the route by which the city of Los Angeles came to be called by that name. Late in life St. Francis retired to a tiny hut on “a little piece of property,” una porziuncola near Assisi. Because angels were frequently heard singing there, the area around his hut was known as “La Valle di Nostra Donna degli Angeli.” Here, Francis experienced two appearances of Mary and her Son, during which he obtained the revolutionary plenary indulgence known as Il Perdono d’Assisi. The Porziuncola became a pilgrims’ shrine, and Francis’s hut was transformed into a huge basilica dedicated to Santa Maria degli Angeli. Reception of the indulgence slowly spread throughout Europe, and most particularly in Spain. Columbus, who was a Franciscan Tertiary, after a stay in the monastery of Our Lady of the Angels at La Rábida, set sail on his momentous journey on the feast of the Perdono (2 August). The indulgence was carried to the New World by the Franciscans where the devotion developed a wide-spread cult. Three hundred years later, the Spanish king’s army, accompanied by Franciscan friars, journeyed up the western coast and came upon a clear stream, which they called la Porciúncula. In 1781, the New World City of the Angels was founded in the cult’s honor.‬